The gospels of the four evangelists, St. Matthew, St. Mark, St. Luke, and St. John. Translated into the language of the Chipewyan Indians of North-West America. - Kirkby, William West, Rev., 1827- trl; British and Foreign Bible Society. (London: printed for the British and Foreign Bible Soc., 1878)
Text entirely in syllabic characters. Mode of access: Internet.